Caracterização de compostos antioxidantes em grãos de diferentes cultivares de cevada (Hordeum vulgare L.) - Bezerra, Aline Sobreira (2009)
Antioxidants are compounds known as free radicals react with and/or reactive oxygen species in order to idle them, preventing the oxidative damage. Many studies have pointed to the imbalance between oxidants and antioxidants as the cause of many diseases and because of the great importance given to this issue, there is a strong demand for studies involving the identification and quantification of compounds with antioxidant activity. This work was then identify and quantify the polyphenolic compounds full of grains of Brazilian cultivars of barley, grown in the municipality of Ibiaçá/RS, in the agricultural year of 2005 and 2006, from the Research Center of Embrapa/Wheat, Passo Fundo/RS and assess the weather conditions (average temperature, precipitation index and insolation) between the time of planting and harvesting barley in the quantification of phenolic compounds between the different seasons. The samples were characterized chemically related to the presence of polyphenols, using the method of separation based on the system of high performance liquid chromatography in reversed phase (RP-HPLC) with UV-VIS detection to 254 nm. We identified the phenolic compounds rutin, caffeic acid, ferulic acid, quercitrin and myricetin, with rutin and caffeic acid the most abundant among cultivars. Alongside was a quantification of phenolic compounds by the Folin-Ciocalteau technique of aiming at a comparison with the chromatographic technique. The techniques have proved satisfactory for the purposes of identification and quantification of differentiation in barley samples analyzed. There was a chemical differentiation of the varieties of barley in relation to polyphenolic compounds identified and quantified and between varieties of different years of cultivation. In the assessment of climatic factors, it was observed that a lower average temperature, a higher rainfall and less sunshine received by barley between planting and harvest seasons, reflected in an increase of total phenols using the Folin-Ciocalteu and quantification of HPLC flavonoid rutin.